Glued diaphragm for lithium ion battery as well as preparation method and application of glued diaphragm
The glue-coated diaphragm for lithium-ion batteries addresses electrolyte wettability and adhesion issues by using a silane coupling agent to reduce PVDF-HFP crystallinity, enhancing room-temperature adhesion and stability without hot pressing, thus improving battery performance.
Patent Information
- Application Number
- CN202411496055.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing lithium-ion battery separators face issues with electrolyte wettability and adhesion at room temperature, leading to inconsistent electrode distances and rapid capacity decay due to the use of PVDF-HFP with high crystallinity and poor adhesion to electrodes.
A glue-coated diaphragm for lithium-ion batteries is developed, comprising a diaphragm substrate with a solid electrolyte coating and a glue layer, where the solid electrolyte coating includes a silane coupling agent to enhance interaction with PVDF-HFP, reducing its crystallinity and improving adhesion at room temperature.
The solution achieves strong adhesion between the diaphragm and electrodes without hot pressing, saving energy and costs while maintaining battery stability by ensuring the glue layer does not fall off during swelling.
Smart Images

Figure CN119231086A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a glue-coated diaphragm for lithium-ion batteries and a preparation method and application thereof. Background Art
[0002] The separators used in lithium-ion secondary batteries are usually high molecular polymer separators such as PE or PP, which are usually poorly wetted by electrolytes. During the manufacturing process of lithium-ion batteries, the rise of electrolyte on the separator will leave wrinkles on the separator through the action of surface tension. Such wrinkles will cause the distance between the positive and negative electrodes to be inconsistent, which will eventually affect the rapid decay of battery capacity.
[0003] In order to solve this problem, alumina ceramics or oxide solid electrolytes are usually used to coat the diaphragm to enhance the wettability of the electrolyte to the diaphragm. In addition, a PVDF-type adhesive layer (such as poly (vinylidene fluoride-co-hexafluoropropylene), abbreviated as PVDF-HFP) is further coated on the inorganic coating by surface coating or spot coating to enhance the adhesion between the diaphragm and the positive and negative electrodes. However, at room temperature, PVDF-HFP itself has high room temperature crystallinity and poor adhesion to the positive and negative electrodes, and needs to be enhanced by hot pressing. In order to save energy consumption and costs, there is an urgent need for an adhesive layer that can achieve good adhesion at room temperature. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a glue-coated diaphragm for lithium-ion batteries and a preparation method and application thereof. The glue-coated diaphragm provided by the present invention has good adhesion at room temperature.
[0005] The present invention provides a glue-coated diaphragm for lithium-ion batteries, comprising: a diaphragm substrate, a solid electrolyte coating coated on the surface of the diaphragm substrate, and a glue layer coated on the surface of the solid electrolyte coating;
[0006] The solid electrolyte coating is formed by coating a solid electrolyte coating and then drying it. The components of the solid electrolyte coating include: a solid electrolyte, a silane coupling agent, a binder, a wetting agent and water;
[0007] The adhesive layer is formed by coating an adhesive solution and then drying the adhesive solution, wherein the adhesive solution comprises: poly(vinylidene fluoride-co-hexafluoropropylene), a binder, a wetting agent and water.
[0008] Preferably, the solid electrolyte is at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate and lithium lanthanum zirconate; the solid electrolyte is a powder, D 50 The particle size is 500~600nm.
[0009] Preferably, the silane coupling agent is at least one of vinyltriethoxysilane, vinyltriacetoxysilane, 3-isocyanatepropyltriethoxysilane, octadecyl-dimethyl-(3-trimethoxysilylpropyl)ammonium chloride, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane and bis-(3-triethoxysilylpropyl)tetrasulfide.
[0010] Preferably, the weight average molecular weight of the poly(vinylidene fluoride-co-hexafluoropropylene) is 400,000 to 500,000.
[0011] Preferably, the binder in the solid electrolyte coating and the glue solution is independently selected from at least one of carboxymethyl acrylate, carboxymethyl cellulose salt, xanthan gum, acrylic acid water-based adhesive, polyacrylamide adhesive and polyvinylidene fluoride adhesive.
[0012] Preferably, the wetting agents in the solid electrolyte coating and the glue are independently selected from at least one of sodium lauryl sulfate, polyether siloxane, fatty alcohol and condensate of ethylene oxide.
[0013] Preferably, the components of the solid electrolyte coating include, by mass, 30 to 40 parts of solid electrolyte, 3 to 5 parts of silane coupling agent, 3 to 5 parts of binder, 0.5 to 0.7 parts of wetting agent and 60 to 70 parts of water.
[0014] Preferably, the adhesive comprises, by weight, 10 to 20 parts of poly(vinylidene fluoride-co-hexafluoropropylene), 3 to 5 parts of a binder, 0.5 to 0.7 parts of a wetting agent and 60 to 70 parts of water.
[0015] The present invention provides a method for preparing the glue-coated diaphragm for lithium-ion batteries described in the above technical solution, comprising the following steps:
[0016] a) coating a solid electrolyte coating on the surface of the diaphragm substrate and drying the coating to form a solid electrolyte coating;
[0017] b) coating the surface of the solid electrolyte coating with glue solution, drying, forming a glue layer, and obtaining a glue-coated diaphragm for a lithium-ion battery.
[0018] The present invention provides a lithium ion battery, which comprises the glue-coated diaphragm for lithium ion battery described in the above technical solution or the glue-coated diaphragm for lithium ion battery prepared by the preparation method described in the above technical solution.
[0019] Compared with the prior art, the present invention provides a coated diaphragm for lithium-ion batteries and a preparation method and application thereof. The coated diaphragm for lithium-ion batteries provided by the present invention comprises: a diaphragm substrate, a solid electrolyte coating coated on the surface of the diaphragm substrate, and a glue layer coated on the surface of the solid electrolyte coating; the solid electrolyte coating is formed by drying after coating the solid electrolyte coating, and the components of the solid electrolyte coating include: a solid electrolyte, a silane coupling agent, a binder, a wetting agent and water; the glue layer is formed by drying after coating the glue liquid, and the components of the glue liquid include: poly (vinylidene fluoride-co-hexafluoropropylene), a binder, a wetting agent and water. The present invention enhances the interaction between the oxide solid electrolyte and the PVDF-HFP glue layer through a silane coupling agent, reduces the crystallinity of the glue layer of the coated diaphragm, and achieves good adhesion of the coated diaphragm to the electrode sheet at room temperature. More specifically, there are usually a large number of high-valent metal cations in the oxide solid electrolyte, which can interact with the electron-rich group F substituent in PVDF-HFP, on the one hand, enhancing the bonding force between the glue layer and the oxide solid electrolyte layer, and on the other hand, reducing the crystallinity of the PVDF-HFP glue layer. However, this interaction is weak and is not enough to make the glue layer have strong adhesion to the positive and negative electrodes at room temperature; while the silane coupling agent can interact with the hydroxyl groups on the surface of the oxide solid electrolyte and the electron-rich sites on the PVDF-HFP polymer chain segment, respectively, so that the glue layer is more evenly and tightly bonded to the solid electrolyte coating, thereby destroying the crystal structure of the glue layer, enhancing its adhesion, and achieving good adhesion between the glue layer and the electrode sheet at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0021] Figure 1 This is a SEM image of a local area of the adhesive layer of Example 1 provided by the present invention;
[0022] Figure 2 This is a SEM image of a local area of the adhesive layer of Comparative Example 1 provided by the present invention. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The present invention provides a glue-coated diaphragm for lithium-ion batteries, comprising: a diaphragm substrate, a solid electrolyte coating coated on the surface of the diaphragm substrate, and a glue layer coated on the surface of the solid electrolyte coating;
[0025] The solid electrolyte coating is formed by coating a solid electrolyte coating and then drying it. The components of the solid electrolyte coating include: a solid electrolyte, a silane coupling agent, a binder, a wetting agent and water;
[0026] The adhesive layer is formed by coating an adhesive solution and then drying the adhesive solution, wherein the adhesive solution comprises: poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), a binder, a wetting agent and water.
[0027] In the glue-coated diaphragm provided by the present invention, the diaphragm substrate includes but is not limited to a polyethylene (PE) film or a polypropylene (PP) film.
[0028] In the glue-coated diaphragm provided by the present invention, the solid electrolyte in the solid electrolyte coating is preferably lithium aluminum titanium phosphate (Li 1.3 Al 0.3 Ti 1.7 (PO4)3, abbreviated as LATP), lithium lanthanum titanate (Li 3x La 2 / 3-x TiO3, abbreviated as LLTO) and lithium lanthanum zirconate (Li7La3Zr2O 12 , abbreviated as LLZO) at least one; the solid electrolyte is preferably a powder, D 50 The particle size is preferably 500-600 nm, and specifically may be 500 nm, 510 nm, 520 nm, 530 nm, 540 nm, 550 nm, 560 nm, 570 nm, 580 nm, 590 nm or 600 nm.
[0029] In the glue-coated diaphragm provided by the present invention, the silane coupling agent in the solid electrolyte coating is preferably at least one of vinyl triethoxysilane, vinyl triacetoxysilane, 3-isocyanate propyl triethoxysilane, octadecyl-dimethyl-(3-trimethoxysilyl) ammonium chloride, γ-mercaptopropyl trimethoxysilane, γ-mercaptopropyl triethoxysilane and bis-(3-triethoxysilyl) tetrasulfide.
[0030] In the glue-coated diaphragm provided by the present invention, the binder in the solid electrolyte coating is preferably at least one of carboxymethyl acrylate, carboxymethyl cellulose salt, xanthan gum, acrylic acid water-based adhesive, polyacrylamide adhesive and polyvinylidene fluoride adhesive.
[0031] In the glue-coated diaphragm provided by the present invention, the wetting agent in the solid electrolyte coating is preferably at least one of sodium dodecyl sulfate, polyether siloxane, aliphatic alcohol and a condensate of ethylene oxide.
[0032] In the glue-coated diaphragm provided by the present invention, the components of the solid electrolyte coating preferably include, by weight: 30 to 40 parts of a solid electrolyte, 3 to 5 parts of a silane coupling agent, 3 to 5 parts of a binder, 0.5 to 0.7 parts of a wetting agent, and 60 to 70 parts of water; wherein the content of the solid electrolyte may be specifically 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts or 40 parts, and the content of the silane coupling agent may be specifically 3 parts, 3.2 parts, 3.5 parts, 3.7 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts or 40 parts, and the content of the silane coupling agent may be specifically 3 parts, 3.2 parts, 3.5 parts, 3.7 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, The content of binder can be specifically 3 parts, 3.2 parts, 3.5 parts, 3.7 parts, 4 parts, 4.2 parts, 4.5 parts, 4.7 parts or 5 parts, the content of wetting agent can be specifically 0.5 parts, 0.52 parts, 0.55 parts, 0.57 parts, 0.6 parts, 0.62 parts, 0.65 parts, 0.67 parts or 0.7 parts, and the content of water can be specifically 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts or 70 parts.
[0033] In the glue-coated diaphragm provided by the present invention, the thickness of the solid electrolyte coating is preferably 0.5 to 3 μm, specifically 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm.
[0034] In the glue-coated diaphragm provided by the present invention, the weight average molecular weight of the poly(vinylidene fluoride-co-hexafluoropropylene) in the glue solution is preferably 400,000 to 500,000, specifically 400,000, 410,000, 420,000, 430,000, 440,000, 450,000, 460,000, 470,000, 480,000, 490,000 or 500,000.
[0035] In the glue-coated diaphragm provided by the present invention, the binder in the glue solution is preferably at least one of carboxymethyl acrylate, carboxymethyl cellulose salt, xanthan gum, acrylic acid water-based adhesive, polyacrylamide adhesive and polyvinylidene fluoride adhesive.
[0036] In the glue-coated diaphragm provided by the present invention, the wetting agent in the glue solution is preferably at least one of sodium lauryl sulfate, polyether siloxane, fatty alcohol and condensate of ethylene oxide.
[0037] In the glue-coated diaphragm provided by the present invention, the components of the glue solution preferably include, by weight: 10 to 20 parts of poly(vinylidene fluoride-co-hexafluoropropylene), 3 to 5 parts of a binder, 0.5 to 0.7 parts of a wetting agent, and 60 to 70 parts of water; wherein the content of poly(vinylidene fluoride-co-hexafluoropropylene) can be specifically 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts, and the content of the binder can be 10 to 20 parts. The content of the agent can be specifically 3 parts, 3.2 parts, 3.5 parts, 3.7 parts, 4 parts, 4.2 parts, 4.5 parts, 4.7 parts or 5 parts, the content of the wetting agent can be specifically 0.5 parts, 0.52 parts, 0.55 parts, 0.57 parts, 0.6 parts, 0.62 parts, 0.65 parts, 0.67 parts or 0.7 parts, and the content of water can be specifically 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts or 70 parts.
[0038] In the glue-coated diaphragm provided by the present invention, the thickness of the glue layer is preferably 0.5-3 μm, specifically 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm.
[0039] The present invention also provides a method for preparing the glue-coated diaphragm for lithium-ion batteries according to the above technical solution, characterized in that it comprises the following steps:
[0040] a) coating a solid electrolyte coating on the surface of the diaphragm substrate and drying the coating to form a solid electrolyte coating;
[0041] b) coating a glue solution on the surface of the solid electrolyte coating, drying the coating to form a glue layer, and obtaining a glue-coated diaphragm for a lithium-ion battery.
[0042] In the preparation method provided by the present invention, in step a), the composition of the solid electrolyte coating has been introduced above and will not be repeated here; the coating method is preferably roller coating; the drying temperature is preferably 40-60°C, specifically 40°C, 45°C, 50°C, 55°C or 60°C.
[0043] In the preparation method provided by the present invention, in step b), the composition of the glue solution has been introduced above and will not be repeated here; the coating method is preferably roller coating; the drying temperature is preferably 50-70°C, specifically 50°C, 55°C, 60°C, 65°C or 70°C.
[0044] The present invention also provides a lithium ion battery, which includes the glue-coated diaphragm for lithium ion battery described in the above technical solution or the glue-coated diaphragm for lithium ion battery prepared by the preparation method described in the above technical solution.
[0045] In the lithium-ion battery provided by the present invention, the glue-coated diaphragm is adhered to an electrode sheet, and the electrode sheet includes but is not limited to a graphite electrode sheet.
[0046] The technical solution provided by the present invention enhances the interaction between the oxide solid electrolyte and the PVDF-HFP adhesive layer through a silane coupling agent, so that the adhesive-coated diaphragm exhibits good adhesion at room temperature. More specifically, the technical solution of the present invention has the following beneficial effects:
[0047] (1) The present invention reduces the crystallinity of the PVDF-HFP adhesive layer and increases its viscosity by the interaction of the oxide solid electrolyte and the silane coupling agent, thereby achieving close contact between the diaphragm and the electrode sheet, avoiding the use of hot pressing equipment, and saving the cost and energy consumption of large-scale production.
[0048] (2) The silane coupling agent used in the present invention interacts with the hydroxyl groups on the surface of the solid electrolyte particles and does not produce a dense coating effect on the solid electrolyte particles. In other words, it does not affect the advantages of the solid electrolyte coating, such as its lithium replenishment effect and hydrofluoric acid removal effect.
[0049] (3) The interaction between the solid electrolyte coating and the glue layer is enhanced by the silane coupling agent. This is a strong interaction. During the operation of the battery, the glue layer will not fall off due to swelling, thus ensuring the stability of the battery operation.
[0050] For the purpose of greater clarity, the present invention is described in detail with reference to the following examples and comparative examples.
[0051] Example 1
[0052] 1. Coating of solid electrolyte coating:
[0053] Deionized water, LLZO powder (granules D 50 500nm), silane coupling agent (3-isocyanatepropyltriethoxysilane, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.), binder (polyacrylamide adhesive, purchased from Hunan Gaorui Power Material Co., Ltd., model GR508), wetting agent (sodium dodecyl sulfate, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.) were mixed in a mass ratio of 70:30:5:5:0.7 to form a solid electrolyte coating. The coating was coated on a PE base film by roller coating and dried in an oven at 50°C. The coating thickness was 2μm.
[0054] 2. Coating of adhesive layer:
[0055] Deionized water, PVDF-HFP (Shanghai Aladdin Biochemical Technology Co., Ltd., product number P304908, weight average molecular weight 400000), binder (polyacrylamide adhesive, purchased from Hunan Gaorui Power Materials Co., Ltd., model GR508), and wetting agent (sodium dodecyl sulfate, purchased from Shanghai McLean Biochemical Technology Co., Ltd.) were mixed uniformly in a mass ratio of 60:20:5:0.7 to form a glue solution, and the glue solution was applied on the above-mentioned solid electrolyte coating by roller coating, and dried in an oven line at 60°C, and the coating thickness was 1 μm.
[0056] 3. Test the peel strength between the glue-coated diaphragm and the electrode:
[0057] The instrument used is a universal tensile testing machine. The diaphragm is cut into strips of 20mm×200mm, and the diaphragm is bonded to a graphite pole piece whose area is much larger than the diaphragm sample by double-sided tape. It is pressed with a pressure of 0.6MPa to simulate the pressurization and hot pressing processes in the battery cell assembly process. The temperature is controlled at 25℃, the graphite pole piece is bonded to a stainless steel plate and fixed on the universal tensile testing machine, the extended edge of the diaphragm sample is pulled apart, the peel force test is completed, and the peel strength is calculated.
[0058] The graphite pole piece used is prepared as follows: the negative electrode active material hard carbon, the conductive agent carbon black, the binder styrene butadiene rubber (SBR), and the thickener sodium hydroxymethyl cellulose (CMC) are dissolved in deionized water at a weight ratio of 96.0:0.9:0.9:1.2 to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on one side of the copper foil current collector, and the negative electrode sheet is obtained after drying, rolling, and slitting.
[0059] Three samples were taken to test the peel strength, which are recorded as Examples 1.1 to 1.3. The results are shown in Table 1.
[0060] 4. Observe the microscopic morphology of the adhesive layer of the adhesive-coated diaphragm:
[0061] The glue layer of the glue-coated diaphragm was observed by scanning electron microscope. Figure 1 shown.
[0062] Comparative Example 1
[0063] 1. Coating of solid electrolyte coating:
[0064] Deionized water, LLZO powder (particle D50 is 500nm), binder (polyacrylamide adhesive purchased from Hunan Gaorui Power Materials Co., Ltd., model GR508), and wetting agent (sodium dodecyl sulfate purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) were evenly mixed in a mass ratio of 70:30:5:0.7 to form a slurry for diaphragm coating. The slurry was coated on the PE base film by roller coating and dried in an oven at 50°C. The coating thickness was 2μm.
[0065] 2. The coating of the adhesive layer is the same as in Example 1, and the coating thickness is 1 μm.
[0066] 3. Take three samples to test the peel strength, record them as comparative examples 1.1 to 1.3, and see Table 1 for the results.
[0067] 4. Observe the microscopic morphology of the adhesive layer of the adhesive-coated diaphragm:
[0068] The glue layer of the glue-coated diaphragm was observed by scanning electron microscope. Figure 2 shown.
[0069] Comparative Example 2
[0070] 1. The coating of the solid electrolyte coating is the same as that of Comparative Example 1, and the coating thickness is 2 μm.
[0071] 2. The coating of the adhesive layer is the same as that of Comparative Example 1, and the coating thickness is 1 μm.
[0072] 3. Take three samples to test the peel strength, but change the 0.6 MPa pressing in the sample preparation process to 0.6 MPa and 80° C. hot pressing, which are recorded as Comparative Examples 2.1 to 2.3. The results are shown in Table 1.
[0073] Test results summary and analysis
[0074] (1) Comparison and analysis of the microstructure of the adhesive layer:
[0075] according to Figure 1 and Figure 2 It can be seen that the silane coupling agent can significantly enhance the interaction between the solid electrolyte and PVDF-HFP, thereby reducing the crystallinity of the polymer; in Comparative Example 1, PVDF-HFP is in a well-crystallized spherical shape, while in Example 1, PVDF is in a continuous distribution state without obvious crystallization performance.
[0076] (2) Comparison and analysis of peel strength of adhesive layer:
[0077] Table 1 Peel strength comparison
[0078]
[0079] In Table 1, Example 1 exhibits higher peel strength than Comparative Example 1, indicating that PVDF-HFP with low crystallinity is conducive to achieving good bonding between the diaphragm and the pole piece at room temperature. Comparative Example 2 uses the same solid electrolyte coating and glue layer as Comparative Example 1, and hot pressing can significantly improve the peel strength between the diaphragm and the pole piece. However, the improved peel strength is still slightly lower than the peel strength in Example 1, indicating that reducing the crystallinity of the glue layer is more effective in enhancing the peel strength between the diaphragm and the pole piece.
[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A coated diaphragm for lithium-ion batteries, characterized in that: include: A diaphragm substrate, a solid electrolyte coating coated on the surface of the diaphragm substrate, and a glue layer coated on the surface of the solid electrolyte coating; The solid electrolyte coating is formed by coating a solid electrolyte coating and then drying it. The components of the solid electrolyte coating include: a solid electrolyte, a silane coupling agent, a binder, a wetting agent and water; The adhesive layer is formed by coating an adhesive solution and then drying the adhesive solution, wherein the adhesive solution comprises: poly(vinylidene fluoride-co-hexafluoropropylene), a binder, a wetting agent and water.
2. The lithium ion battery coated diaphragm according to claim 1, characterized in that: The solid electrolyte is at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate and lithium lanthanum zirconate; the solid electrolyte is a powder, D 50 The particle size is 500~600nm.
3. The glue-coated separator for lithium-ion batteries according to claim 1, characterized in that: The silane coupling agent is at least one of vinyl triethoxysilane, vinyl triacetoxysilane, 3-isocyanate propyl triethoxysilane, octadecyl-dimethyl-(3-trimethoxysilyl) ammonium chloride, γ-mercaptopropyl trimethoxysilane, γ-mercaptopropyl triethoxysilane and bis-(3-triethoxysilyl) tetrasulfide.
4. The glue-coated separator for lithium-ion batteries according to claim 1, characterized in that: The weight average molecular weight of the poly(vinylidene fluoride-co-hexafluoropropylene) is 400,000 to 500,000.
5. The glue-coated separator for lithium-ion batteries according to claim 1, characterized in that: The binder in the solid electrolyte coating and the glue solution is independently selected from at least one of carboxymethyl acrylate, carboxymethyl cellulose salt, xanthan gum, acrylic acid water-based adhesive, polyacrylamide adhesive and polyvinylidene fluoride adhesive.
6. The glue-coated separator for lithium-ion batteries according to claim 1, characterized in that: The wetting agent in the solid electrolyte coating and the glue solution is independently selected from at least one of sodium lauryl sulfate, polyether siloxane, fatty alcohol and condensate of ethylene oxide.
7. The lithium ion battery coated diaphragm according to claim 1, characterized in that: The components of the solid electrolyte coating include, by weight: 30 to 40 parts of solid electrolyte, 3 to 5 parts of silane coupling agent, 3 to 5 parts of binder, 0.5 to 0.7 parts of wetting agent and 60 to 70 parts of water.
8. The glue-coated separator for lithium-ion batteries according to claim 1, characterized in that: The adhesive solution comprises, by weight, 10 to 20 parts of poly(vinylidene fluoride-co-hexafluoropropylene), 3 to 5 parts of a binder, 0.5 to 0.7 parts of a wetting agent and 60 to 70 parts of water.
9. A method for preparing a coated diaphragm for lithium ion batteries according to any one of claims 1 to 8, characterized in that: The following steps are involved: a) coating a solid electrolyte coating on the surface of the diaphragm substrate and drying the coating to form a solid electrolyte coating; b) coating a glue solution on the surface of the solid electrolyte coating, drying the coating to form a glue layer, and obtaining a glue-coated diaphragm for a lithium-ion battery.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the glue-coated diaphragm for lithium-ion battery according to any one of claims 1 to 8 or the glue-coated diaphragm for lithium-ion battery prepared by the preparation method according to claim 9.
Citation Information
Patent Citations
Solid electrolyte film material, preparation method thereof, and battery
CN110148778A
Coated ion and electron mixed conductor diaphragm and preparation method and application thereof
CN115842217A
Gel polymer electrolyte and method for preparing same
CN117059889A
Solid electrolyte coated diaphragm as well as preparation method and application thereof
CN118472555A
Cited By
Solid electrolyte diaphragm, preparation method and lithium ion battery
CN119944239A
Battery separator and electrochemical apparatus comprising same
WO2026179358A1
